PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY DISERTAI TEKNIK ROUNDHOUSE UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI-IPA III SMA NEGERI 1 TERAS BOYOLALI TAHUN AJARAN 2011/2012 - Tri Rukmana, Hantyan Galih; Suciati, Suciati; Indrowati, Meti (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT ? The purpose of this research was to improve the motivation and achievement of students in class XI-IPA III of SMA Negeri 1 Teras Boyolali in the academic year 2011/2012 through the implementation of Guided Inquiry learning model with Roundhouse techniques in learning Biology. This reseach was a Classroom Action Research. The reseach was conducted in several cycles, consisiting of planning, action, observation, and reflection to the subjects which were the eleventh grade students of SMA Negeri 1 Teras in the academic year 2011/2012. The data was collected through questionnaires, observation, tests, and interviews. In analyzing the data, the researcher used several methods: the motivational data validation used triangulation observer, and the cognitive learning outcomes used logical validations which were content and construct, while the affective and psychomotor observer used observation sheets. The data was analyzed by descriptive qualitative method. The result of the research showed that according to the data observation sheet, questionnaire ,and test results, the average percentage of motivational aspect increased from 68.91% in pre-cycle to 73.58% in cycle I and had improved to 76.40% in cycle II. In terms of cognitive learning achievement, it increased from 65.22% in pre-cycle to 71.71% in cycle I and had improved to 83.42% in cycle II. In terms of affective learning, it increased from 53.67% in pre-cycle to 72.31% in cycle I and had improved to 82.17% in cycle II. In terms of psychomotor learning, it was 71.19% in cycle I and increased to 78.09% in cycle II. The conclusion of this research is the application of Guided Inquiry learning model with roundhouse technique can improve the motivation and learning outcomes of students in class XI-IPA III of SMA Negeri 1 Teras Boyolali in the academic year 2011/2012. Keywords: Learning motivation, Learning Outcomes, Guided Inquiry with Roundhouse technique